2019
DOI: 10.5219/1134
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of infrared drying condition for whole duku fruit using response surface methodology

Abstract: Duku (Lansium domesticum), tropical exotic fruit, was successfully preserved by drying using exposure to infrared radiation emitters. Response surface methodology (RSM) is used to optimize independent variables (IRE distance of 6 cm and 10 cm, IRE temperature of 200 °C, 300 °C, 400 °C, and IRE exposure time of 50 s, 60 s, 70 s, and to produce response variables (weight loss, fruit firmness, titratable acidity, total soluble solid, and browning index).  It could be concluded from the optimization performed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Desirability function of 0.771 was obtained at the end of the optimization as shown in Figure 8. This result was rated above average since desirability usually ranged between zero and one (Rahmawati et al., 2019).…”
Section: Resultsmentioning
confidence: 95%
“…Desirability function of 0.771 was obtained at the end of the optimization as shown in Figure 8. This result was rated above average since desirability usually ranged between zero and one (Rahmawati et al., 2019).…”
Section: Resultsmentioning
confidence: 95%
“…The desirability value obtained for the optimization process was 0.838 as shown in Figure 10. The desirability usually range from zero to one, and therefore, expected to be equal to one in an ideal situation (Rahmawati, Saputra, Sahim, & Priyanto, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The desirability value obtained for the optimization process was 0.838 as shown in Figure 10. The desirability usually range from zero to F I G U R E 9 2D Plot effect of pre-drying treatments on color difference F I G U R E 1 0 Optimization results of process conditions in an RSM one, and therefore, expected to be equal to one in an ideal situation (Rahmawati, Saputra, Sahim, & Priyanto, 2019).…”
Section: Optimization Of Drying Conditions For Tomatomentioning
confidence: 99%
“…These values displayed a good signal-to-noise ratio. The signal-to-noise ratio greater than 4 is optimal for acceptable precision (Rahmawati, Saputra, Sahim, & Priyanto, 2019). It was concluded that the model could be used to optimize and navigate the research design.…”
Section: Effect Of Birep On the Total Phenolic Content And Antioxidmentioning
confidence: 99%